Better Correlation of Cognitive Function to White Matter Integrity than to Blood Supply in Subjects with Leukoaraiosis - Zhong, Genlong; Zhang, Ruiting; Jiaerken, Yerfan; Yu, Xinfeng; Zhou, Ying; Liu, Chang; Lin, Longting; Tong, Lusha; Lou, Min (Frontiers in Aging Neuroscience, 2017)
Leukoaraiosis is associated with increased risk of cognitive impairment, but its pathophysiological pathway is unclear. The aim of the present study was to determine whether brain structural damage or cerebral blood supply better correlated with the global cognitive outcome in subjects with leukoaraiosis.Seventy-five subjects with leukoaraiosis were included in present study, with age ranged from 43-85 years, with mean WMH volume 30.69±24.35ml. Among them, 19(25.33%) subjects presented with cerebral microbleeds (CMB) and 40 (53.33%) subjects presented with lacunes. These participants received arterial spin labeling (ASL) perfusion MRI, diffusion-tensor imaging (DTI) and diffusion Kurtosis imaging (DKI). We analyzed the cerebral blood flow (CBF) by dividing the brain tissue into three regions: white matter hyperintensities (WMH), normal appearing white matter (NAWM) and cortex. After adjusting for age and gender, the CBF of NAWM was significantly correlated with fractional anisotropy (FA) (r=0.336, p=0.004) and mean diffusion (MD) (r=-0.271, p=0.020) of NAWM, while there lacked of association between CBF of cortex and mean kurtosis (MK) of cortex (r=-0.015, p=0.912). Meanwhile, both NAWM-FA (r=-0.443, p<0.001) and NAWM-MD (r=0.293, p=0.012), as well as cortex-MK (r=-0.341, p=0.012) was significantly correlated with WMH volume. Univariate regression analysis demonstrated that global cognitive function was significantly associated with mean FA or MD of both WMH and NAWM, and cortex-CBF, but neither with the cortex-MK, nor the presences of CMB or lacunes. Finally, multiple linear regression analysis revealed that global cognitive function was independently associated with NAWM-FA( standardizedβ=0.403, p<0.001) and WMH-FA (Standardizedβ=0.211, p=0.017), but not with the cortex-CBF. A model that contained NAWM-FA, WMH-FA and years of education explained 49% of the variance of global cognitive function. Cerebral perfusion status might have a significant impact on the maintenance of white matter integrity in subjects with leukoaraiosis. Global cognitive function was more strongly associated with white matter integrity than with blood supply. DTI parameters, especially FA could serve as a potent imaging indicator for detecting the invisible alteration of white matter integrity and implying its potential cognitive relevance.